PERSPECTIVE ON UTILIZATION OF PRIMARY HEALTH CARE CENTRE IN RURAL AREAS OF KARNATAKA (International Journal of Food and Nutritional Sciences, 2021)
India has a vast public health infrastructure with 23,391 primary health centers (PHCs) and145,894 sub centers providing health services to 72.2% of the country's population living in ruralareas. Although the numbers look impressive, their functional status needs to be studied in termsof physical infrastructure, manpower, equipment, drugs, and other logistical supplies that aregreatly needed for ensuring quality services.